A Novel 53-kDa Nodulin of the Symbiosome Membrane of Soybean Nodules, Controlled by Bradyrhizobium japonicum - Till Winzer; Andrea Bairl; Monica Linder; Dietmar Linder; Dietrich Werner; Peter Müller (Molecular Plant-Microbe Interactions, 1999)
A nodule-specific 53-kDa protein (GmNOD53b) of the symbiosome membrane from soybean was isolated and its LysC digestion products were microsequenced. cDNA clones of this novel nodulin, obtained from cDNA library screening with an RT-PCR (reverse-transcriptase polymerase chain reaction)-generated hybridization probe exhibited no homology to proteins identified so far. The expression of GmNOD53b coincides with the onset of nitrogen fixation. Therefore, it is a late nodulin. Among other changes, the GmNOD53b is significantly reduced in nodules infected with the Bradyrhizobium japonicum mutant 184 on the protein level as well as on the level of mRNA expression, compared with the wild-type infected nodules. The reduction of GmNOD53b mRNA is related to an inactivation of the sipF gene in B. japonicum 184, coding for a functionally active signal peptidase.